“PROSPECTS OF APPLICATION OF MODERN TECHNOLOGIES IN EDUCATIONAL INSTITUTIONS” - Nurillayev , Ilhom Xolbek o‘g‘li (Educational Research in Universal Sciences, 2023)
About 795 million people on Earth, or one in nine people, are malnourished. Unfortunately, most of them live in developing countries. All this shows us the existing problems in agriculture. If we analyze the fundamental nature of these problems, we can see that the basis of most of the problems is several problems in the field of agricultural education. Therefore, the article includes ideas for improving the education system in the field of agriculture based on modern technologies and innovative technologies. In this article, we analyze several new technologies. Let’s take a look at a few problems. These are ways to improve existing food security, such as genetic modification, methods to improve soil fertility and irrigation technologies. Agriculture is a very favorable environment for innovation.